2018
DOI: 10.1038/s41467-018-07138-5
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood investment impacts social decision-making four decades later

Abstract: Early childhood educational investment produces positive effects on cognitive and non-cognitive skills, health, and socio-economic success. However, the effects of such interventions on social decision-making later in life are unknown. We recalled participants from one of the oldest randomized controlled studies of early childhood investment—the Abecedarian Project (ABC)—to participate in well-validated interactive economic games that probe social norm enforcement and planning. We show that in a repeated-play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Camisasca et al, 2017;Giovanelli et al, 2020;Marchetti et al, 2020) and extending to subsequent, significant affective relationships (Bowlby, 1969(Bowlby, , 1973(Bowlby, , 1980. It has been suggested that children's decision to place trust in an unknown informant, especially in a context of uncertainty, may also depend on generalizing from their personal attachment history (Fonagy, 1998;Allison and Fonagy, 2016;Fonagy et al, 2019;see also, Bo et al, 2017;Luo et al, 2018). For example, securely attached children are more flexible in establishing trustful relationships with epistemically reliable strangers than children with a fragile relational past (see, for example, .…”
Section: Introductionmentioning
confidence: 99%
“…Camisasca et al, 2017;Giovanelli et al, 2020;Marchetti et al, 2020) and extending to subsequent, significant affective relationships (Bowlby, 1969(Bowlby, , 1973(Bowlby, , 1980. It has been suggested that children's decision to place trust in an unknown informant, especially in a context of uncertainty, may also depend on generalizing from their personal attachment history (Fonagy, 1998;Allison and Fonagy, 2016;Fonagy et al, 2019;see also, Bo et al, 2017;Luo et al, 2018). For example, securely attached children are more flexible in establishing trustful relationships with epistemically reliable strangers than children with a fragile relational past (see, for example, .…”
Section: Introductionmentioning
confidence: 99%
“…Investment in education at the early stages produces long-term benefits in decision-making (Luo et al, 2018), but must be accompanied by policies that foster innovative approaches at the level of teacher training. An observational study in rural Tarija, the most Southern region of Bolivia, registered several concerning behaviors in teachers that would be considered unacceptable in most countries: favoritism, lack of interest, and unexcused absence from the classroom (Punch, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Investment in education at the early stages produces long-term benefits in decision-making [49]. Yet, this investment needs to be accompanied with policies that focus on training teachers on innovative approaches to education.…”
Section: Discussionmentioning
confidence: 99%